In Situ Growth of Robust 2D ZIF‐67 MOF in Block Copolymer Membranes for Ultrafast Molecular Degradation - Jingjing Xu; Jianyong Yu; Leiming Guo; Faxue Li; Nikos Hadjichristidis (Advanced Science)
Abstract Membrane‐based advanced oxidation processes (AOPs) rely heavily on the configuration of membrane structures and catalysts. However, designing state‐of‐the‐art membrane structures integrated with tailored catalysts for efficient AOPs remains a significant challenge. In this study, for the first time, hybrid membranes are constructed by the in situ growth of 2D ZIF‐67 onto the nanopore walls of 3D block copolymer (BCP) membranes. These membranes feature highly tunable pore structures, leading to exceptional catalytic performance that surpasses previously reported membranes. The remarkable catalytic efficiency stems from the predominant role of the non‐radical species, 1O2, in catalytic degradation, combined with the integration of the high‐surface‐area 2D ZIF‐67 and the tortuous pore structures of the BCP membranes. The resulting catalytic membranes demonstrate robust performance, achieving stable permeance of over 1800 L (m2·bar·h)−1 while completely degrading dyes during long‐term filtration. Notably, the degradation efficiency is maintained at 90% even when the permeance is adjusted to 3070 L (m2·bar·h)−1. Additionally, the membranes exhibit excellent resistance to both alkali and acidic environments and are unaffected by various background anions or the types of degraded molecules. This work presents a novel approach to designing advanced catalytic membranes for high‐efficiency, space‐confined AOPs.